Studies With Staggered Starts: Multiple Baseline Designs and Group-Randomized Trials - Rhoda, Dale A. (American Public Health Association, 2011)
Objectives. Multiple baseline designs (MBDs) have been suggested as alternatives to group-randomized trials (GRT). We reviewed structural features of MBDs and considered their potential effectiveness in public health research. We also reviewed the effect of staggered starts on statistical power. Methods. We reviewed the MBD literature to identify key structural features, recent suggestions that MBDs be adopted in public health research, and the literature on power in GRTs with staggered starts. We also computed power for MBDs and GRTs. Results. The features that have contributed to the success of small MBDs in some fields are not likely to translate well to public health research. MBDs can be more powerful than GRTs under some conditions, but those conditions involve assumptions that require careful evaluation in practice. Conclusions. MBDs will often serve better as a complement of rather than as an alternative to GRTs. GRTs may employ staggered starts for logistical or ethical reasons, but this will always increase their duration and will often increase their cost.